The Influence of Brand Image and Service Quality on Purchasing Decisions for Milk Coffee Products at Toko Kopi Bersaudara in Mojokerto City - Putra, Euniko Tri Laksana (PT FORMOSA CENDEKIA GLOBAL, 2024)
The limitations of the problem in this research include purchasing decisions which are influenced by brand image variables and service quality variables. In conducting this research, the sample used was the Instagram followers of the Café Bersaudara Mojokerto. Research Objectives: To find out and analyze the influence of brand image on the decision to purchase milk coffee at Bersaudara cafe. To find out and analyze the quality of service regarding the decision to purchase milk coffee at the Bersaudara cafe. To find out and analyze the influence of brand image and service quality on the decision to purchase milk coffee at Bersaudara cafe. The company must have a brand that is different from its competitors, as well as the brand image that is embedded in the minds of customers. Because brand image is one of the first things that customers see before making a purchase or selecting a product. Cafe Bersaudara always maintains its popularity, quality service in a timely manner, and affordable prices so that consumers always decide to make purchases at Cafe Bersaudara. In the first hypothesis test, it was discovered that Brand Image partially had a positive and significant effect on the Purchase Decision for Milk Coffee Products at Cafe Bersaudara. In the second hypothesis test, it was discovered that the Service Quality variable partially had a positive and significant effect on the decision to purchase milk coffee products at the Bersaudara Cafe. In the third hypothesis test, it was discovered that the Brand Image and Service Quality variables simultaneously had a positive and significant influence on the decision to purchase milk coffee products at Cafe Bersaudara. Thus, it can be said that the hypothesis in this research has been proven positively and significantly for each variable used